Inspiring song: The role of respiratory circuitry in the evolution of vertebrate vocal behavior. Issue 1 (19th May 2020) - Barkan, Charlotte L.; Zornik, Erik
Abstract: Vocalization is a common means of communication across vertebrates, but the evolutionary origins of the neural circuits controlling these behaviors are not clear. Peripheral mechanisms of sound production vary widely: fish produce sounds with a swimbladder or pectoral fins; amphibians, reptiles, and mammalians vocalize using a larynx; birds vocalize with a syrinx. Despite the diversity of vocal effectors across taxa, there are many similarities in the neural circuits underlying the control of these organs. Do similarities in vocal circuit structure and function indicate that vocal behaviors first arose in a single common ancestor, or have similar neural circuits arisen independently multiple times during evolution? In this review, we describe the hindbrain circuits that are involved in vocal production across vertebrates. Given that vocalization depends on respiration in most tetrapods, it is not surprising that vocal and respiratory hindbrain circuits across distantly related species are anatomically intermingled and functionally linked. Such vocal‐respiratory circuit integration supports the hypothesis that vocal evolution involved the expansion and functional diversification of breathing circuits. Recent phylogenetic analyses, however, suggest vocal behaviors arose independently in all major tetrapod clades, indicating that similarities in vocal control circuits are the result of repeated co‐options of respiratory circuits in each lineage. It is currently unknown whether vocal circuits across taxa are made up of homologous neurons, or whether vocal neurons in each lineage arose from developmentally and evolutionarily distinct progenitors. Integrative comparative studies of vocal neurons across brain regions and taxa will be required to distinguish between these two scenarios.